Comprehensive Analysis on the Influence of Flap Width on the Hydrodynamic Parameters of OWSC Devices - Rasya Aulia Nathania Nisa; James Julian; Fitri Wahyuni; Riki Hendra Purba; Fathin Muhammad Mahdhudhu; Elvi Armadani (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
The growing need for renewable energy has driven significant interest in harnessing ocean wave power, particularly through Oscillating Wave Surge Converters (OWSCs). This study focuses on examining the effect of flap width on the hydrodynamic capacity of an OWSC, as flap geometry plays a crucial role in energy capture efficiency. A numerical methodology utilizing the Boundary Element Method (BEM) was employed to assess hydrodynamic parameters across both temporal and frequency domains. Five flap width variations were tested under regular wave conditions with different periods, while mesh independence and validation against experimental data ensured accuracy. The results in the time domain revealed a direct correlation between flap width and angular deviation, velocity, torque, and power output, although wider flaps exhibited less stability due to increased inertia. Frequency domain analysis indicated that each flap width had a distinct resonant peak, with narrower flaps performing best at shorter periods and wider flaps at longer ones. Notably, moderately sized flaps (W2 and W3) achieved the highest efficiency, with Capture Width Ratios exceeding 70%, outperforming wider flaps despite their larger surface area. These findings highlight the importance of optimized flap width for efficient and reliable OWSC design.